Awareness and attitude of mothers of primary school children towards child sexual abuse in Tamil Nadu, India - Shirley, S. Alph; Kumar, S. Santha (International Journal of Contemporary Pediatrics, 2019)
Background: Child sexual abuse leads to several adverse impacts in the affected children. A study on awareness and attitude of mothers towards child sexual abuse will help to formulate better techniques to improve awareness and prevent child sexual abuse. The objective is to study the awareness and attitude of mothers of primary school students towards child sexual abuse. Methods: This cross-sectional observational study was done in the state of Tamil Nadu, India among 186 mothers of primary school children. Data were collected from the mothers using a predesigned questionnaire and analyzed. Results: Only 12.9% of the mothers were aware of the POCSO Act and 32.8% were aware of the child helpline 1098. 76.9% of the mothers were aware of unexplained genital injury as a physical indicator of child sexual abuse. Acute traumatic response (83.9%) and regression in behavior (82.8%) were the commonly aware behavioral indicators of child sexual abuse. Only 25.3% of the mothers believed that boys can be sexually abused. 75.3% of the mothers believed that the offenders were usually unknown persons. 88.7% of the mothers believed that unaccompanied children were a risk factor. 88.2 % of the mother believed that physical and mental disability in children was a risk factor. Majority of the mothers believed that streets (88.7%) and institutions (80.1%) were the common environment for child sexual abuse. Only 23.7% of the mothers had taught regarding good touch and bad touch to their children. 50.5 % of the mothers believed that the major role in preventing child sexual abuse is played by the parents. Conclusions: Awareness regarding child sexual abuse was low among the mothers of primary school children.